2013
DOI: 10.3389/fcimb.2013.00085
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of streptococcal plasminogen binding proteins with the host fibrinolytic system

Abstract: The ability to take advantage of plasminogen and its activated form plasmin is a common mechanism used by commensal as well as pathogenic bacteria in interaction with their respective host. Hence, a huge variety of plasminogen binding proteins and activation mechanisms exist. This review solely focuses on the genus Streptococcus and, in particular, on the so-called non-activating plasminogen binding proteins. Based on structural and functional differences, as well as on their mode of surface linkaging, three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 93 publications
0
42
0
Order By: Relevance
“…We recently identified SCM as an M protein of S. canis , characterized by its affinity for the serum protein plasminogen and its anti-phagocytic properties (Fulde et al, 2011, 2013a,b). In the present study, we were interested in determining whether the SCM protein might possess additional binding activities to other serum proteins with immune-modulatory functions, in particular immunoglobulin G. We, therefore, incubated different SCM-positive and-negative S. canis strains with iodinated rabbit IgG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently identified SCM as an M protein of S. canis , characterized by its affinity for the serum protein plasminogen and its anti-phagocytic properties (Fulde et al, 2011, 2013a,b). In the present study, we were interested in determining whether the SCM protein might possess additional binding activities to other serum proteins with immune-modulatory functions, in particular immunoglobulin G. We, therefore, incubated different SCM-positive and-negative S. canis strains with iodinated rabbit IgG.…”
Section: Resultsmentioning
confidence: 99%
“…In prior studies, we had identified plasminogen (PLG) as a ligand for SCM (Fulde et al, 2011, 2013a,b). The detection of IgG as an additional binding partner for SCM inevitably raised the question as to whether PLG and IgG compete for the same binding site on SCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of enolase from Streptococcus pneumoniae described an internal plasminogen binding motif (termed BS2) ''FYDKERKVY'' and its C-terminal lysines (termed BS1) [9] as factors in the enzyme's ability to bind plasminogen. Subsequent work described the impact this plasminogen affinity had on the fibrinolytic system [10], and suggested its dependence on lysine interactions with plasminogen [11,12]. This internal plasminogen binding motif is conserved in enolases of many other organisms [13][14][15], including the enolase described here.…”
Section: Introductionmentioning
confidence: 73%
“…The affinity of plasminogen's kringle domains for lysines is thought to be a factor in binding interactions with enolase [12], and at least in the case of an enolase from S. suis, the binding of fibronectin may have some dependence on lysines [22]. In the octameric assembly of enolase from L. gasseri, only 3 of the 22 available lysine residues per monomer are buried within the interfaces, leaving 19 per monomer exposed on the surface.…”
Section: Discussionmentioning
confidence: 99%